IMPROVING STUDENTS’ MASTERY OF THE SIMPLE PAST TENSE BY USING CHINESE WHISPERS AND GROUP GRID TECHNIQUE (ELT Forum: Journal of English Language Teaching, 2015)
The eleventh graders of PGRI 2 Private Vocational School Salatiga were obliged to master the simple past tense since one of the basic competences in school-based curriculum was about telling activities or works in the past and future work plans. Unfortunately, they still possessed low mastery of grammar and experienced difficulties in learning it. A classroom action research about the use of Chinese whispers and group grid technique aimed to resolve those emerging problems with the foci of the study to investigate how this method could be used in teaching the simple past tense, and how the use of it improved students’ mastery of the simple past tense. Specifically, the subject of this study was 34 students of class XI D at PGRI 2 Private Vocational School Salatiga in the academic year of 2014/2015. This study was conducted in two cycles in a total of seven meetings. The instruments for obtaining the data were tests, observation sheet, and questionnaire. The observation sheet results showed that students’ behaviors and responses during the learning processes improved and became relatively good. Furthermore, the questionnaire results indicated that students tended to show good judgment on the implementation of this teaching method. The final result of the study revealed that there was a significant improvement in students’ achievement. Their average score in pre-test was 58.65, in formative test 1 was 76.97, in formative test 2 was 79.06, and in post-test was 83.56. Referring to the overall results of the study, the combination of Chinese whispers and group grid technique could be considered as one of alternative and effective teaching methods to improve students’ mastery of the simple past tense.